Reforms in the history of the curriculum in Venezuela (XII Education and social change in Latin America and the ancient world) - Garcia, José Pascual Mora (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The approaching to the curriculum as a topic of research linked to the social history of the curriculum goes through a preliminary look of epistemological status. The epistemological approach of the curriculum history must transcend the equal view of the discipline that abounded in the schools and in the specialists of the curriculum. Integrate the study of how it was built the intellectual field of the curriculum, in a national and international level. We propose to answers to the following questions: what are the main reforms, the main foundational concepts and when did they enter into the national education system? When was it taken into account by the Ministry of Education of Venezuela? How was built the curricular speech in universities, research centers, research groups, and even national associations of teachers, among others? When did it impact directly in the chair since archaeological history of the disciplines of the school? but especially, showing the results of these researches linked with the local, regional, national and international networks.